Size distribution and sex ratio between populations of the artisanal harvested land crab Cardisoma guanhumi (Decapoda: Gecarcinidae), with the estimation of relative growth and size at sexual maturity in Puerto Rico - Quiñones-Llópiz, Jesús D.; Rodríguez-Fourquet, Concepción; Luppi, Tomás; Farias, Nahuel E. (Revista de Biología Tropical, 2021)
Introduction: Knowledge of growth patterns, sex ratio, and sexual maturity are of importance to exploited populations. The land crab Cardisoma guanhumi is an artisanal and subsistence exploited species in Puerto Rico. However, the growth patterns and sexual maturity of the local populations are not known. Objectives: This study has a double objective: (1) to compare the size and sex structure between populations and (2) to model the relative growth of structures related to reproduction to estimate the average size of morphometric sexual maturity (MSM) for both males and females. Methods: A total of 2 849 specimens were captured from nine dispersed populations on the island between 2001 and 2020. Carapace width (CW) was measured as an estimator of the absolute size of all individuals, together with the propodus length (PL) in males and the abdomen width in females (AW). Differences in length structure between sexes and populations were tested by applying goodness-of-fit tests based on Kernel Density Estimators (KDE). The relative growth pattern was modeled adjusting a spline from which the maximum of its second derivative was calculated as an estimator of the MSM, and bootstrapping was used to generate confidence intervals. Results: Differences were found in size structures, between sexes, and between sites. Our estimates of morphometric sexual maturity resulted in a sexual maturity size for males between 57.9 and 79.0 mm CW, while in females, morphological maturity occurs between 43.8 to 51.5 mm CW. Conclusions: We found inter-population differences in body size that can be attributed to differences in the history of changes of land use and the exploitation biased towards larger individuals, though differences in recruitment should also be considered. Current regulations in Puerto Rico protect female crabs but not to larger male crabs. The regulation establishes that crabs smaller than 64 mm carapace width cannot be captured, leaving immature male crabs over 64 mm CW unprotected. We suggest considering different size limits depending on the sex of the crab. This will allow the full range of sizes where sexual maturity is reached to be protected, increasing the likelihood of the population’s size to increase.